Levantamento florístico e distribuição vertical de epífitas vasculares sobre Aldina heterophylla Spruce ex Benth - Mari, Maikel Lamego Guimarães (Instituto Nacional de Pesquisas da Amazônia - INPA, 2014)
Surveys of vascular holoepiphytes were conducted in three campinarana forests where epiphytes were raised in 36 phorophytes (Aldina heterophylla), 12 in each area, with DBH ≥ 20 cm, and 360 saplings, 10 around each host tree with DBH ≤ 10cm. In the surveys were noted areas of occurrence of epiphytes: Zone 1 - basal part of the stem (0- 2m); Zone 2 - stem up to the first branch, disregarding isolated branches below the canopy, also divided into wetland (2a) and dry zone (2b); Zone 3 - basal part of large branches (first third) until the first branch; Zone 4 - Second-third of the branches; Zone 5 - Third of external branch length for larger diameter phorophytes; while the incidence in young trees was considered a distinct area, S. Zone. Structural parameters were calculated and dimensionality of the species composition of epiphytic between phorophytes was reduced by Principal Coordinates Analysis (PCoA). The effects of site, area and dimension (reason DBH:height) of the host tree on the attributes of the community (richness, diversity and floristic composition) were tested through hierarchical ANCOVA models with nested area within the site and the reason DBH: height as covariate. In the results of surveys of 36 major phorophytes, were recorded 5922 epiphytes, distributed in eight families, 34 genera and 71 species. The monocotyledonous were represented by four families and 62 species (87.3% ), while eudicotyledonous by two families and three species (4.2%) and fern with two families and six species (8.4%). On saplings 612 epiphytes, distributed in 5 families, 24 genera and 38 species were recorded. The three most important species by VIE were: Elaphoglossum glabellum (10.3 %), Elaphoglossum auricomum (6.4 %) and Camaridium ochroleucum (6.2 %). The greatest densities of epiphytes occurred in canopy zones (3, 4 and 5), being in zone 3 the greatest number of individuals. The floristic composition between A. heterophylla and saplings was dissimilar, with only two species (out of 73) occurring exclusively in saplings. The proportion of variance attributed to two hierarchical factors and covariate jointly differ for the different attributes of the community and the level of explanation of the hierarchical factors differ between individual attributes. For the composition of epiphytes (PCoA axis 1 and axis 2), 73-78 % of the variance was explained by site, zone and reason DAP x height. In this case, the first two were highly significant, with most of the area explaining the variation of the gradient along the first axis defined by the composition of the PCoA and, instead, site explained most of the variation along the axis 2 of the PCoA, also significantly explaining the diversity (Fisher 's alpha), while species richness was best explained by area. The epiphytic stratum of the three investigated campinaranas proved quite distinct between areas and there was a clear separation in floristic composition between areas of crown and bole of phorophytes.
Keywords: Epífitas; Aldina heterophylla; Estratificação vertical; Campinarana